On becoming whole in "Pentecostal spirituality" : the quest for an integrative approach to pastoral caregiving and healing - Roux, Lee-Anne (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.